Skeletal defects and bone metabolism in Noonan, Costello and cardio-facio-cutaneous syndromes - Papadopoulou, Anna; Bountouvi, Evangelia (Frontiers in Endocrinology, 2023)
Noonan, Costello and Cardio-facio-cutaneous syndromes belong to a group of disorders named RASopathies due to their common pathogenetic origin that lies on the Ras/MAPK signalling pathway. Genetics has eased, at least in part, the distinction of these entities as they are presented with overlapping clinical features which, sometimes, become more pronounced with age. Distinctive face, cardiac and skeletal defects are among the primary abnormalities seen in these patients. Skeletal dysmorphisms range from mild to severe and may include anterior chest wall anomalies, scoliosis, kyphosis, short stature, hand anomalies, muscle weakness, osteopenia or/and osteoporosis. Patients usually have increased serum concentrations of bone resorption markers, while markers of bone formation are within normal range. The causative molecular defects encompass the members of the Ras/MAPK/ERK pathway and the adjacent cascades, important for the maintenance of normal bone homeostasis. It has been suggested that modulation of the expression of specific molecules involved in the processes of bone remodelling may affect the osteogenic fate decision, potentially, bringing out new pharmaceutical targets. Currently, the laboratory imprint of bone metabolism on the clinical picture of the affected individuals is not clear, maybe due to the rarity of these syndromes, the small number of the recruited patients and the methods used for the description of their clinical and biochemical